Benefits and adverse events in younger versus older patients receiving neoadjuvant chemotherapy for osteosarcoma: findings from a meta-analysis - Collins, Marnie; Wilhelm, Miriam; Conyers, Rachel; Herschtal, Alan; Whelan, Jeremy; Bielack, Stefan; Kager, Leo; Kühne, Thomas; Sydes, Matthew; Gelderblom, Hans; Ferrari, Stefano; Picci, Piero; et al. (Journal of clinical oncology, 2013)
The LIVESTRONG Young Adult Alliance has conducted a meta-analysis of individual patient data from prospective neoadjuvant chemotherapy osteosarcoma studies and registries to examine the relationships of sex, age, and toxicity on survival. Suitable data sets were identified by a survey of published data reported in PubMed. The final pooled data set comprised 4,838 patients from five international cooperative groups. After accounting for important variables known at study entry such as tumor location and histology, females experienced higher overall survival rates than males (P = .005) and children fared better than adolescents and adults (P = .002). Multivariate landmark analysis following surgery indicated that a higher rate of chemotherapy-induced tumor necrosis was associated with longer survival (P < .001), as was female sex (P = .004) and the incidence of grade 3 or 4 mucositis (P = .03). Age group was not statistically significant in this landmark analysis (P = .12). Females reported higher rates of grade 3 or 4 thrombocytopenia relative to males (P < .001). Children reported the highest rates of grade 3 or 4 neutropenia (P < .001) and thrombocytopenia (P < .001). The achievement of good tumor necrosis was higher for females than for males (P = .002) and for children than for adults (P < .001). These results suggest fundamental differences in the way chemotherapy is handled by females compared with males and by children compared with older populations. These differences may influence survival in a disease in which chemotherapy is critical to overall outcomes.